Comparative study of quality of life and surgical outcome in open mastoid cavity and mastoid cavity obliteration in canal wall down mastoidectomy - Maheshwari, Sumit; Kumar, Ravish; Nagle, Smita K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Canal wall down mastoidectomy is a surgical technique used for the eradication of middle ear disease. The remaining large mastoid bowl is associated with a number of issues; one of the techniques that have been developed in order to avoid such problems is the obliteration of the mastoid cavity. Mastoid obliteration resulted in a decrease in the complications associated with the open mastoid cavity. The materials used for this reason are either biological or synthetic. Mastoid obliteration with synthetic materials is a valuable and safe surgical technique for patients who undergo canal wall down mastoidectomy. Methods: This is a prospective study carried out in the department of otorhinolaryngology. Sample size: 30 patients out of which 15 were operated by Modified Radical Mastoidectomy with obliteration (Group A) and 15 were operated by Modified Radical Mastoidectomy without obliteration (Group B). Study design: single centre, longitudinal, prospective, two group, parallel, follow-up, randomly allocated statistical method and tools: Fischer’s Exact Test. Study period: August 2017 to August 2020. Results: Study was divided in two groups, group A (modified radical mastoidectomy with obliteration) & group B (modified radical mastoidectomy without obliteration). Conclusions: The incidence of pain, discharge, giddiness and wax formation was markedly reduced in obliterated cavities as compared to open cavities. Healing of the cavity as evidenced by epithelialization, at the end of 3 months, was better in obliterated ears. Patients with obliterated mastoid cavity required less cavity care, doctor dependence, frequent OPD visits.